L1CAM further stratifies endometrial carcinoma patients with no specific molecular risk profile - Kommoss, Felix (British journal of cancer, 2018)
The newly developed Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) has consistently been shown to be prognostically significant in endometrial carcinomas (EC). Recently, we and others have demonstrated L1 cell-adhesion molecule (L1CAM) to be a significant indicator of high-risk disease in EC. In the current study, it was our aim to determine the prognostic significance of aberrant L1CAM expression in ProMisE subgroups in a large, single centre, population-based EC cohort.
Gesehen am 16.12.2019